HEARTHSTONE COTTAGE - Lee, Frazer (London : FLAME TREE PRESS, 2019)
"Mike Carter and his girlfriend Helen, along with their friends Alex and Kay, travel to a remote loch side cottage for a post-graduation holiday. But their celebrations are short-lived when they hit and kill a stag on the road. Alex's sister Meggie awaits them in the cottage, adding to the tension when her dog, Oscar, goes missing. Mike becomes haunted by a disturbing presence in the cottage, and is hunted by threatening figures in the highland fog. Reeling from a shock revelation, Mike begins to lose his grip on his sanity. As the dark secrets of the past conspire to destroy the bonds of friendship, Mike must uncover the terrifying truth dwelling within the walls of Hearthstone Cottage."--Provided by publisher.
Keywords: Vacations -- Fiction; Haunted places -- Fiction; Secrecy -- Fiction; Horror fiction; Psychological fiction; Thrillers (Fiction)